Silicon carbide negative electrode material and preparation method thereof

By introducing single-wall carbon nanotubes into silicon carbide particles to form a flexible network skeleton and covering carbon powder and lithiated perfluorosulfonic acid resin on the outside, the volume expansion and cyclic performance of silicon carbide negative electrode materials during charging and discharging are solved. The poor problem achieves better electrochemical performance.

CN118782779BActive Publication Date: 2025-02-07河南中新绿动能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411239390.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-02-07
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The silicon carbide negative electrode material expands in large volume and poor circulation performance during charging and discharging, which affects the electrochemical performance.

Method used

By introducing single-wall carbon nanotubes into silicon carbide particles, a flexible network skeleton is formed, which binds silicon carbide, limits its deformation, and coats carbon powder and lithiated perfluorosulfonic acid resin on the outside of the particles to improve conductivity and structural stability .

Benefits of technology

The volume expansion of the silicon carbide negative electrode material during charging and discharging is significantly reduced, and the circulation performance and battery rate performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118782779B_ABST
    Figure CN118782779B_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon carbide negative electrode material, comprising silicon carbide particles, and single-walled carbon nanotubes inside the silicon carbide particles are interlaced and entangled to form a flexible network skeleton to constrain silicon carbide. The present invention also discloses a method for preparing the silicon carbide negative electrode material, comprising the following steps: mixing a polydimethylsiloxane prepolymer and a single-walled carbon nanotube slurry; adding a curing agent and curing at 80±5°C for 3 to 5 hours after removing bubbles in a vacuum oven with a vacuum degree of ≤-90kPa; reacting the obtained cross-linked polymer at 450 to 600°C and a vacuum degree of ≤-90kPa for 6 to 10 hours to obtain a polycarbosilane melt; the polycarbosilane melt is melt-spun, sintered, and granulated under an inert atmosphere at a negative pressure of 0.04 to 0.06MPa to obtain silicon carbide particles. In the silicon carbide negative electrode material of the present invention, single-walled carbon nanotubes are interlaced and entangled to form a flexible network skeleton to constrain silicon carbide, limit deformation, and improve volume expansion and contraction and powder cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a silicon carbide negative electrode material and a preparation method thereof. Background Art

[0002] As a new generation of negative electrode materials for lithium-ion batteries, silicon-based negative electrodes have a capacity of up to 4200mAh / g, which is more than 10 times that of graphite negative electrode materials. They are the most promising negative electrode materials for the next generation of lithium-ion batteries. Silicon-based negative electrodes also have shortcomings that are difficult to overcome, which are mainly due to the serious volume expansion of silicon-based negative electrodes during the lithium insertion process. In the fully lithium-intercalated state, the volume expansion of silicon-based negative electrodes can reach 300%, which will cause the material particles to pulverize and fall off, seriously affecting their electrochemical performance. At present, one of the main methods to improve the volume expansion of silicon-based negative electrodes is to nano-size silicon materials, such as nano-films, nano-wires, nano-particles, etc. Although nano-sized silicon can better release the stress caused by volume changes and provide space for volume expansion, due to the low intrinsic conductivity of silicon, nano-sized silicon will still have a more obvious capacity decay after multiple cycles, and the battery power density is also low.

[0003] Silicon carbide has attracted much attention as a new type of negative electrode material, and has great potential due to its high specific capacity and excellent chemical stability. It can store more lithium ions and improve battery energy density, while having faster electron transmission speed and better electrochemical performance, and is expected to meet the needs of high-performance batteries. However, silicon carbide negative electrode materials still face problems such as volume expansion, pulverization, and poor cycle performance. Summary of the invention

[0004] The purpose of the present invention is to provide a silicon carbide negative electrode material for a lithium ion battery with small volume expansion and good cycle performance during charging and discharging.

[0005] The technical solution of the present invention is:

[0006] A silicon carbide negative electrode material comprises silicon carbide particles, wherein single-walled carbon nanotubes are arranged inside the silicon carbide particles, and the single-walled carbon nanotubes are interlaced and entangled to form a flexible network skeleton to bind the silicon carbide.

[0007] The silicon carbide negative electrode material of the present invention has a flexible network skeleton formed by the interlacing and winding of single-walled carbon nanotubes in silicon carbide particles, which three-dimensionally limits the deformation of silicon carbide and improves its volume expansion and contraction and powder cracking during the charging and discharging process when used as an electrode material; and the network formed by it can improve the conductivity of silicon carbide and improve the rate performance of the battery made therefrom.

[0008] Preferably, the outside of the silicon carbide particles is coated with carbon powder, and the carbon powder is bonded by a lithiated perfluorosulfonic acid resin. More preferably, the carbon powder is graphite. The silicon carbide negative electrode material coated with carbon powder not only improves the conductivity, but also avoids direct contact with the electrolyte when used in the battery, thereby improving the structural stability. The lithiated perfluorosulfonic acid resin is bonded and wrapped on the surface of each silicon carbide particle, and is evenly distributed, which can replenish the lithium consumed when the SEI film is formed in the battery, and the ion conductivity of the lithiated perfluorosulfonic acid resin itself makes the prepared battery have better rate performance.

[0009] The present invention also provides a method for preparing a silicon carbide negative electrode material, comprising the following steps:

[0010] Step 1, uniformly mixing polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 4-15:0.0016-0.006;

[0011] Step 2, adding a curing agent and mixing evenly, placing in a vacuum oven, evacuating to remove bubbles, the vacuum degree of the oven is ≤-90 kPa, curing at 80±5°C for 3 to 5 hours, to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes;

[0012] Step 3, reacting the cross-linked polymer at 450-600° C. and vacuum degree ≤-90 kPa for 6-10 hours to obtain a polycarbosilane melt;

[0013] Step 4: melt-spin the obtained polycarbosilane melt under the protection of an inert atmosphere and a negative pressure of 0.04 to 0.06 MPa, continuously feed the wire, sinter, and granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; wherein the wire feeding speed is 1 to 10 m / min, the sintering temperature is 1000 to 1500°C, and the sintering time is 2 to 6 hours.

[0014] In the preparation method of the silicon carbide negative electrode material of the present invention, the mixing of the polydimethylsiloxane prepolymer and the single-walled carbon nanotube slurry can be carried out by stirring, ultrasonic waves, etc. The concentration of the single-walled carbon nanotube slurry can be selected and used as needed, for example, a commercially available single-walled carbon nanotube slurry with a solid content of 0.4% can be used. By fully mixing the polydimethylsiloxane prepolymer and the single-walled carbon nanotube in a mass ratio of 4 to 15:0.0016-0.006 in step one, the single-walled carbon nanotube is fully dispersed and stretched in the polydimethylsiloxane prepolymer. After the polymerization in step two, the single-walled carbon nanotube is interlaced, entangled and fixed in the cross-linked structure of the polydimethylsiloxane formed by the polymerization; after the reaction in step three, the Si-Si bond in the polydimethylsiloxane is broken and rearranged, converted into a Si-C bond, and a low molecular weight carbosilane is generated; as the temperature continues to rise, dehydrogenation and demethanization condensation reactions occur between carbosilane molecules to gradually increase the molecular weight to generate polycarbosilane. During the reaction, the single-walled carbon nanotubes are interlaced, entangled and stay in the cross-linked structure of the polycarbosilane melt, and then melt-spinned in step four. The filamentation process of melt spinning causes the material to be stretched longitudinally at high temperature and contracted radially, thereby forming a polycarbosilane fiber with stronger radial constraint and higher mechanical strength in the length direction. In such a polycarbosilane fiber structure, the single-walled carbon nanotubes are interlaced, entangled and bound to the polycarbosilane. After sintering at 1000-1500°C for 2-6 hours, the polycarbosilane is inorganically transformed into silicon carbide, while the single-walled carbon nanotubes still interlace and entangle the silicon carbide. Due to the stretching process of melt spinning, the silicon carbide material prepared has a higher inward constraint in the radial direction of the fiber, a higher mechanical strength in the axial direction, and the posture of the single-walled carbon nanotubes in the silicon carbide is also moderately adjusted, and it is more inclined to constrain the mechanical deformation of silicon carbide from the radial direction. When the silicon carbide particles thus prepared are used, the granular material is arranged in random directions, which can improve its volume expansion and contraction and powder cracking during battery charging and discharging. In particular, single-walled carbon nanotubes have high mechanical strength, low density and fine structure, so that they are widely distributed in silicon carbide materials even when used in small quantities, forming an interlaced and entangled network structure, becoming the carbonaceous flexible skeleton of silicon carbide materials, and limiting the deformation of silicon carbide in three-dimensional and multi-dimensional ways, improving its volume expansion and contraction and powder cracking during the charging and discharging process when used as an electrode material; and the network it forms can improve the conductivity of silicon carbide and improve the rate performance of batteries made from it.

[0015] The inert atmosphere in step 4 may be a nitrogen atmosphere, an argon atmosphere, or the like.

[0016] Preferably, the single-walled carbon nanotube has a diameter of 1 to 3 nm, a length of 2 to 5 μm, and an aspect ratio of 1000 to 5000.

[0017] Preferably, the mass ratio of the curing agent to the polydimethylsiloxane prepolymer is 0.8 to 1.2: 10. Adding the curing agent in this ratio allows the polydimethylsiloxane prepolymer to fully react with the curing agent, leaving the reactants at a minimum, thereby minimizing the undesirable impurities in the product and achieving optimal performance.

[0018] Preferably, the diameter of the particles obtained by granulation in step 4 is 0.5-20 μm, and the length is 0.5-20 μm. The particles of this size are preferably appropriately graded according to size.

[0019] Preferably, the method for preparing the silicon carbide negative electrode material comprises the following steps:

[0020] Step 5, mixing the granules obtained by granulation with carbon powder and lithium perfluorosulfonic acid resin in a mass ratio of 1:0.5-2:0.02-0.1, adding an organic solvent to fully disperse them, and heating at 80-100°C for 4-6h; wherein the carbon powder is natural graphite or artificial graphite, and its D 50 More preferably, the organic solvent is N-methylpyrrolidone.

[0021] Through step five, the obtained silicon carbide material particles having a flexible network skeleton structure formed by interlacing and winding single-walled carbon nanotubes are evenly dispersed in the solution with carbon powder and lithiated perfluorosulfonic acid resin, and heated at 80-100° C. for 4-6 hours to reduce the residual solvent to a minimum, thereby forming a carbon coating layer on the outside of the silicon carbide particles.

[0022] The fluorine atoms and sulfonate groups in the lithium perfluorosulfonic acid resin are both strongly polar groups, which makes it have strong adhesion, so that the carbon powder and the silicon carbide particles are firmly bonded, and a restraining layer is formed on the outside of the silicon carbide particles to restrict its volume expansion, limiting its expansion; it is also beneficial to the combination between the negative electrode active material and the current collector. The lithium perfluorosulfonic acid resin in the carbon coating layer outside the silicon carbide particles has the characteristics of lithium ion conduction due to the presence of sulfonate groups, which is beneficial to the transmission of lithium ions, thereby improving the dynamic performance of lithium-ion batteries; the lithium it contains can supplement the lithium consumed by the entire lithium-ion battery during the cycle process, improving the battery's capacity retention rate.

[0023] In the preparation process of step 5, heating at 80-100°C for 4-6 hours can make the solvent evaporate completely at a moderate speed, preventing the solvent from evaporating too quickly to form a concentration gradient and cracks. At the same time, it does not affect the strong adhesion of fluorine atoms and sulfonate groups in the lithium perfluorosulfonic acid resin, maintains a high adhesion between fiber particles and carbon powder, and improves the stability of the carbon powder coating layer. The silicon carbide negative electrode material coated with carbon powder can avoid direct contact with the electrolyte when used in the battery, which improves the structural stability and conductivity of the material.

[0024] The beneficial effects of the present invention are:

[0025] The silicon carbide negative electrode material of the present invention has a flexible network skeleton formed by the interlacing and winding of single-walled carbon nanotubes in silicon carbide particles to constrain silicon carbide, and the deformation of silicon carbide is limited in three dimensions, thereby improving the expansion and contraction of its volume and the cracking of powder during the charging and discharging process when it is used as an electrode material. The method for preparing the silicon carbide negative electrode material of the present invention is to uniformly disperse the single-walled carbon nanotubes in the polydimethylsiloxane prepolymer and fully disperse and stretch the single-walled carbon nanotubes so that the single-walled carbon nanotubes are interlaced and fixed in the cross-linked structure of the intermediate product polydimethylsiloxane, and then further radial contraction and longitudinal stretching are obtained in the formed polycarbosilane fibers, forming polycarbosilane fibers with stronger radial constraint and higher mechanical strength in the length direction. After sintering, the silicon carbide material prepared has a higher inward constraint in the radial direction, a higher mechanical strength in the axial direction and is constrained by the network structure of the interlaced and wound single-walled carbon nanotubes, which limits the expansion and contraction of its volume and the cracking of powder during the charging and discharging process when it is used as an electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the silicon carbide negative electrode material prepared in Example 2 of the present invention.

[0027] In the figure: 1. Silicon carbide negative electrode material; 2. Carbon powder; 3. Silicon carbide particles; 301. Single-walled carbon nanotubes. DETAILED DESCRIPTION

[0028] The present invention is described in detail below with reference to the examples. The polydimethylsiloxane prepolymer used in the following examples is a commercial product, for example, SYLGARD 184 produced by Dow Corning, USA, and its corresponding curing agent.

[0029] Example 1

[0030] A silicon carbide negative electrode material is prepared as follows:

[0031] Step 1: Evenly mix polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 1:0.0006; the solid content of the single-walled carbon nanotube slurry is 0.4%, the diameter of the single-walled carbon nanotube is 1-3nm, the length is 2-5μm, and the aspect ratio is 1000-5000.

[0032] Step 2: Add curing agent with a mass ratio of curing agent to polydimethylsiloxane prepolymer of 1:10, mix well, place in a vacuum oven, evacuate to remove bubbles, the vacuum degree of the oven is ≤-90kPa, and cure at 80±5℃ for 4h to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes.

[0033] Step 3: reacting the cross-linked polymer at 450-500° C. and vacuum degree ≤-90 kPa for 8 hours to obtain a polycarbosilane melt.

[0034] Step 4: melt-spin the obtained polycarbosilane melt under the protection of nitrogen atmosphere and under the condition of negative pressure of 0.05 MPa, and continuously feed the wire at a feeding speed of 5 m / min. Sinter at 1200-1250°C for 3 hours. Granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; the particle diameter is 5-7 μm and the length is 0.5-20 μm.

[0035] Example 2

[0036] A silicon carbide negative electrode material is prepared. In the preparation method, steps 1 to 4 are exactly the same as those in Example 1, and the method further includes step 5:

[0037] The obtained silicon carbide particles are mixed with D 50 1 part by mass and 0.5 part by mass of artificial graphite powder with a diameter of 4.0 μm were taken respectively, and 1.5 parts by mass of N-methylpyrrolidone were added and mixed to form a thin slurry. After sufficient mechanical stirring, ultrasonic waves were used to fully disperse the mixture, and the mixture was heated at 80°C for 4 hours to remove the solvent N-methylpyrrolidone. The product was ground and sieved to obtain D 50 It is a silicon carbide negative electrode material with a thickness of 8.3μm. Figure 1 Schematic diagram of the structure of the silicon carbide negative electrode material prepared in this embodiment, as shown in Figure 1 As shown, the silicon carbide negative electrode material 1 prepared in this embodiment comprises silicon carbide particles 3, wherein the silicon carbide particles 3 have single-walled carbon nanotubes 301 inside, wherein the single-walled carbon nanotubes 301 are interlaced and entangled to form a flexible network skeleton to bind the silicon carbide. The outside of the silicon carbide particles 3 is coated with carbon powder 2.

[0038] Example 3

[0039] A silicon carbide negative electrode material is prepared. In the preparation method, steps 1 to 4 are exactly the same as those in Example 1, and the method further includes step 5:

[0040] The obtained silicon carbide particles are mixed with D 50 1 part by mass, 0.5 part by mass, and 0.05 part by mass of artificial graphite powder with a diameter of 4.0 μm and lithium perfluorosulfonic acid resin were respectively taken and mixed, 1.5 parts by mass of N-methylpyrrolidone was added and mixed evenly to form a thin slurry, after sufficient mechanical stirring, ultrasonic dispersion was used to fully disperse, heated at 80°C for 4h, the solvent N-methylpyrrolidone was removed, and the product was ground and sieved to obtain D 50 It is a silicon carbide negative electrode material with a thickness of 8.2μm.

[0041] Example 4

[0042] A silicon carbide negative electrode material is prepared as follows:

[0043] Step 1: Evenly mix polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 1:0.0015; the solid content of the single-walled carbon nanotube slurry is 0.4%, the diameter of the single-walled carbon nanotube is 1-3nm, the length is 2-5μm, and the aspect ratio is 1000-5000.

[0044] Step 2: Add curing agent with a mass ratio of curing agent to polydimethylsiloxane prepolymer of 0.8:10, mix well, place in a vacuum oven, evacuate to remove bubbles, the vacuum degree of the oven is ≤-90kPa, and cure at 80±5℃ for 3h to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes.

[0045] Step 3: reacting the cross-linked polymer at 550-600° C. and vacuum degree ≤-90 kPa for 6 hours to obtain a polycarbosilane melt.

[0046] Step 4: melt-spin the obtained polycarbosilane melt under the protection of nitrogen atmosphere and under the condition of negative pressure of 0.04 MPa, and continuously feed the wire at a feeding speed of 5 m / min. Sinter at 1000-1050°C for 5 hours. Granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; the diameter of the particles is 5-7 μm and the length is 0.5-20 μm.

[0047] Step 5: Mix the obtained silicon carbide particles with D 50 1 part by mass, 2 parts by mass, and 0.05 parts by mass of artificial graphite powder with a diameter of 6.0 μm and lithium perfluorosulfonic acid resin were respectively mixed, 3 parts by mass of N-methylpyrrolidone was added and mixed evenly to form a thin slurry, after sufficient mechanical stirring, ultrasonic dispersion was used to fully disperse, heated at 100° C. for 6 h, the solvent N-methylpyrrolidone was removed, and the product was ground and sieved to obtain D 50 It is a silicon carbide negative electrode material with a thickness of 8.3μm.

[0048] Example 5

[0049] A silicon carbide negative electrode material is prepared as follows:

[0050] Step 1: Evenly mix polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 15:0.0016; the solid content of the single-walled carbon nanotube slurry is 0.4%, the diameter of the single-walled carbon nanotube is 1-3 nm, the length is 2-5 μm, and the aspect ratio is 1000-5000.

[0051] Step 2: Add curing agent, the mass ratio of curing agent to polydimethylsiloxane prepolymer is 1.2:10, mix well, place in a vacuum oven, evacuate to remove bubbles, the vacuum degree of the oven is ≤-90kPa, and cure at 80±5℃ for 5h to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes.

[0052] Step 3: reacting the cross-linked polymer at 500-550° C. and vacuum degree ≤-90 kPa for 6 hours to obtain a polycarbosilane melt.

[0053] Step 4: melt-spin the obtained polycarbosilane melt under nitrogen atmosphere protection and negative pressure of 0.06 MPa, and continuously feed the wire at a feeding speed of 10 m / min. Sinter at 1450-1500°C for 6 hours. Granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; the diameter of the particles is 0.5-0.7 μm and the length is 0.5-20 μm.

[0054] Step 5: Mix the obtained silicon carbide particles with D 50 1 mass part, 1 mass part, and 0.02 mass part of natural graphite powder with a diameter of 5.0 μm and lithium perfluorosulfonic acid resin were respectively taken and mixed, 2 mass parts of N-methylpyrrolidone were added to make a thin slurry, after sufficient mechanical stirring, ultrasonic dispersion was used to disperse it uniformly, heated at 90°C for 5h, the solvent N-methylpyrrolidone was removed, and the product was ground and sieved to obtain D 50 It is a silicon carbide negative electrode material with a thickness of 8.4μm.

[0055] Example 6

[0056] A silicon carbide negative electrode material is prepared as follows:

[0057] Step 1: Evenly mix polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 15:0.0016; the solid content of the single-walled carbon nanotube slurry is 0.4%, the diameter of the single-walled carbon nanotube is 1-3 nm, the length is 2-5 μm, and the aspect ratio is 1000-5000.

[0058] Step 2: Add curing agent, the mass ratio of curing agent to polydimethylsiloxane prepolymer is 1.2:10, mix well, place in a vacuum oven, evacuate to remove bubbles, the vacuum degree of the oven is ≤-90kPa, and cure at 80±5℃ for 5h to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes.

[0059] Step 3: reacting the cross-linked polymer at 500-550° C. and vacuum degree ≤-90 kPa for 6 hours to obtain a polycarbosilane melt.

[0060] Step 4: melt-spin the obtained polycarbosilane melt under nitrogen atmosphere protection and negative pressure of 0.06 MPa, and continuously feed the wire at a feeding speed of 2 m / min. Sinter at 1450-1500°C for 2 hours. Granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; the diameter of the particles is 14-16 μm and the length is 0.5-20 μm.

[0061] Step 5: Mix the obtained silicon carbide particles with D 50 1 part, 0.5 part and 0.1 part of natural graphite powder with a diameter of 5.0 μm and lithium perfluorosulfonic acid resin were taken, 1.5 parts by mass of N-methylpyrrolidone was added to make a thin slurry, after sufficient mechanical stirring, ultrasonic dispersion was used to disperse the mixture uniformly, heated at 90°C for 5h, the solvent N-methylpyrrolidone was removed, and the product was ground and sieved to obtain D 50 It is a 16.5μm silicon carbide negative electrode material.

[0062] Comparative Example 1

[0063] A silicon carbide negative electrode material was prepared. The difference between the preparation method and Example 2 was that in step 1, multi-walled carbon nanotubes of the same mass were used instead of single-walled carbon nanotubes, the solid content of the multi-walled carbon nanotube slurry was 12.5%, the diameter of the multi-walled carbon nanotubes was 20-50 nm, and the length was 5-30 μm. Steps 2 to 5 were exactly the same as in Example 2.

[0064] Comparative Example 2

[0065] A silicon carbide negative electrode material was prepared, and the difference between the preparation method and Example 2 was that the single-walled carbon nanotube slurry was replaced with superconducting carbon black of the same mass in step 1. Steps 2 to 5 were exactly the same as those in Example 2.

[0066] Comparative Example 3

[0067] A silicon carbide negative electrode material is prepared. The preparation method is different from that of Example 2 in that steps 1, 2 and 4 are:

[0068] In step 1 of this comparative example, the same mass of polydimethylsiloxane prepolymer and single-walled carbon nanotubes as in Example 2 were weighed respectively. The single-walled carbon nanotubes were used in step 4; in step 2, a curing agent was directly added to the polydimethylsiloxane prepolymer, and the other operations of step 2 were the same as in Example 2, and step 3 was also exactly the same as in Example 2.

[0069] Step 4 of this comparative example is as follows:

[0070] Step 4: Cool the obtained polycarbosilane melt, crush and sieve to obtain a powder with a particle size less than 20 μm.

[0071] The obtained polycarbosilane powder is added with xylene, and dispersed evenly by ultrasonication to obtain a polycarbosilane solution; the weighed single-walled carbon nanotubes are then added to the polycarbosilane solution, and dispersed evenly by ultrasonication again to obtain a spinning solution.

[0072] Under a nitrogen pressure of 0.2 MPa, the spinning solution is extruded from a spinneret at 102°C through a metering pump into fibers and enters the spinning tunnel. Nitrogen is introduced into the tunnel to take away the volatilized xylene. The filament bundle is wound on a spinning cylinder. The winding speed is 2 m / min, and polycarbosilane fibers with a diameter of 5 to 7 μm are obtained. The obtained polycarbosilane fibers are sintered at 1200 to 1250°C for 3 hours. Granulation is performed to produce silicon carbide particles with single-walled carbon nanotubes inside; the diameter of the particles is 5 to 7 μm and the length is 0.5 to 20 μm.

[0073] Step 5 is exactly the same as in Example 2 to obtain D 50 It is a silicon carbide negative electrode material with a thickness of 8.3μm.

[0074] Performance testing:

[0075] The silicon carbide negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were used to prepare lithium ion batteries and perform performance tests, respectively, as follows:

[0076] 1. Battery Preparation

[0077] The silicon carbide negative electrode materials prepared in the above examples 1-6 and comparative examples 1-3 were used to prepare lithium ion batteries respectively, and the methods were as follows:

[0078] Take 95.0 parts by mass of silicon carbide negative electrode material, add 200 parts of an aqueous solution containing 5.0 parts by mass of CMC / SP / PAA (mass ratio 0.5:2.0:2.5) thereto, and mix to form a slurry;

[0079] 2. The slurry is coated on a copper foil with a thickness of 6 μm, dried, and rolled to form an electrode sheet. The thickness of the electrode sheet after pressing is tested and recorded, and recorded as W1.

[0080] 3. Lithium foil was used as the counter electrode to form a soft-pack lithium-ion battery with the copper foil electrode prepared above. The electrolyte used was a solution containing solvents ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1) and 1 mol / L lithium hexafluorophosphate electrolyte. A three-layer microporous diaphragm of polypropylene / polyethylene / polypropylene (PP / PE / PP) was used with a thickness of 20 μm.

[0081] 2. Performance Testing

[0082] 1. The first discharge capacity and first coulombic efficiency of the lithium-ion battery prepared above were measured at room temperature. The results are shown in Table 1. The current density of charge / discharge was 0.6 mA / cm 2 The cut-off charge and discharge voltages are 2.000V and 0.005V.

[0083] 2. Test the capacity retention rate for 100 weeks

[0084] Charge / discharge at a current density of 0.6 mA / cm 2 The cut-off charge and discharge voltage was 2.000V and 0.005V, and the charge and discharge were tested at room temperature for 100 cycles. The results were recorded and the capacity retention rate after 100 cycles was calculated. The calculation results are recorded in Table 1.

[0085] 3. Expansion rate test:

[0086] After 100 cycles of charge and discharge, the lithium-ion battery was disassembled and the electrode sheet thickness was tested, recorded as W2, and the electrode sheet expansion rate was calculated and recorded in Table 1.

[0087] Electrode sheet expansion rate = (W2-W1) / W1×100%.

[0088] Examples First discharge specific capacity (mAh / g) First coulombic efficiency (%) Capacity retention rate after 100 cycles (%) Electrode sheet expansion rate (%) Example 1 1242.80 87.91 75.26 43.5 Example 2 958.20 88.48 82.51 40.32 Example 3 990.67 90.54 86.24 37.51 Example 4 680.67 91.72 89.53 35.46 Example 5 585.90 91.98 92.84 42.78 Example 6 993.33 90.23 84.22 43.02 Comparative Example 1 983.40 87.42 71.17 46.66 Comparative Example 2 985.38 88.02 68.41 47.34 Comparative Example 3 966.44 88.67 64.29 49.58

[0089] From the results in Table 1, we can see that:

[0090] The capacity retention rate of lithium-ion batteries made of silicon carbide negative electrode materials prepared by Examples 1 to 6 of the method of the present invention after 100 cycles is all above 75%, and the battery electrode sheet expansion rate is all below 43.5%. The volume expansion of the lithium-ion battery during the charge and discharge process is small and the cycle performance is good. However, the volume expansion of silicon carbide negative electrode materials not prepared by the method of the present invention is large and the cycle performance is poor. For example: Although the only difference between Comparative Example 1 and Example 2 is that multi-walled carbon nanotube slurry is used instead of single-walled carbon nanotube slurry in step 1, the capacity retention rate of the lithium-ion battery prepared thereby after 100 cycles is 71.17%, which is lower than 82.51% of Example 2; the battery electrode sheet expansion rate is 46.66%, which is much higher than 40.32% of Example 2. For another example, although the difference between Comparative Example 2 and Example 2 is that superconducting carbon black is used instead of single-walled carbon nanotube slurry in step 1, the capacity retention rate of the lithium-ion battery made therefrom after 100 cycles is 68.41%, which is much lower than 82.51% of Example 2; the battery electrode sheet expansion rate is 47.34%, which is much higher than 40.32% of Example 2. It can be seen that the binding of silicon carbide by single-walled carbon nanotubes with the same mass ratio is much better than that of multi-walled carbon nanotubes or superconducting carbon black. Single-walled carbon nanotubes with the same mass ratio are not only numerous, but also easier to form a dense binding network; and because single-walled carbon nanotubes have better mechanical properties, they can better limit the mechanical deformation of silicon carbide, while superconducting carbon black cannot form a binding network at all; the relative number of multi-walled carbon nanotubes is small, and the mechanical properties are not good.

[0091] It can also be seen from Table 1 that the capacity retention rate of the lithium-ion battery made in Comparative Example 3 after 100 cycles is 64.29%, which is much lower than 82.51% in Example 2; the battery pole piece expansion rate is 49.58%, which is much higher than 40.32% in Example 2. The difference between Comparative Example 3 and Example 2 lies in the addition method of single-walled carbon nanotubes and the spinning method after the polycarbosilane melt is made. The single-walled carbon nanotubes in Comparative Example 3 are added to the polycarbosilane solution after the polycarbosilane melt is made; while Example 2 using the method of the present invention adds the single-walled carbon nanotubes to the polydimethylsiloxane prepolymer for dispersion; Comparative Example 3 performs spinning of the polycarbosilane solution followed by sintering and granulation to obtain silicon carbide; while the example using the method of the present invention adopts melt spinning of the polycarbosilane melt followed by sintering and granulation to obtain silicon carbide. It can be seen that the method of the present invention adds the single-walled carbon nanotube slurry to the polydimethylsiloxane prepolymer, so that the single-walled carbon nanotubes are fully dispersed and stretched in the polydimethylsiloxane prepolymer. After the polymerization in step two, the single-walled carbon nanotubes are interlaced, entangled and fixed in the cross-linked structure of polydimethylsiloxane; after the reaction and melt spinning in steps three and four, the single-walled carbon nanotubes in the polycarbosilane fiber structure are interlaced, entangled and bound to the polycarbosilane, and after further inorganicization, the single-walled carbon nanotubes are interlaced, entangled and bound to the silicon carbide. However, the dispersion of the single-walled carbon nanotubes in the polycarbosilane solution in Comparative Example 3, no matter how it is dispersed, is not as dispersed and stretched as the molecular structure of the polycarbosilane in the cross-linked manner in the method of the present invention. The single-walled carbon nanotubes in the silicon carbide prepared in this way are difficult to form an effective network structure to bind the silicon carbide. Therefore, the prepared silicon carbide negative electrode material cannot well limit the volume expansion during the cycle, and the capacity retention rate of the cyclic charge and discharge is not very ideal. In addition, the stretching of the polycarbosilane melt during the melt spinning process causes the material to shrink radially, forming polycarbosilane fibers with stronger radial restraint and higher mechanical strength in the length direction, which also improves the performance of the silicon carbide negative electrode material prepared after inorganicization.

[0092] It can also be seen from the test results of each embodiment in Table 1 that the use of lithium perfluorosulfonic acid resin and carbon powder to coat silicon carbide particles can further improve the volume expansion of silicon carbide negative electrode materials during the charge and discharge process and improve the capacity retention rate. This can be seen from the test results of Example 3 and Example 2. Lithium perfluorosulfonic acid resin was not used in the carbon coating performed in Example 2, while lithium perfluorosulfonic acid resin was added during the carbon coating process in Example 3. The first charge and discharge specific capacity of the battery made of the silicon carbide negative electrode material prepared in this way was also increased from 958.20 mAh / g in Example 2 to 990.67 mAh / g, and the first coulomb efficiency was increased from 88.48% in Example 2 to 90.54%. It can be seen that the lithium perfluorosulfonic acid resin effectively supplements the lithium consumed by the formation of the SEI film during the first charge and discharge process, thereby improving the electrical performance. In addition, as can be seen from Table 1, the first discharge specific capacity of the negative electrode material of Example 1 without coating is much larger than that of Example 2 with carbon coating. It can be seen that due to the large proportion of silicon material in the silicon carbide negative electrode material of Example 1, its specific capacity is much larger, which shows that silicon material has a high specific capacity. The silicon carbide negative electrode material prepared by the method of the present invention has small volume expansion and good cycle performance, which provides support for better application of silicon-based negative electrode materials in lithium-ion batteries.

[0093] It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

Claims

1. A method for preparing a silicon carbide negative electrode material, characterized in that: The following steps are involved: Step 1, uniformly mixing polydimethylsiloxane prepolymer and single-walled carbon nanotube slurry; wherein the mass ratio of polydimethylsiloxane prepolymer to single-walled carbon nanotube is 4-15:0.0016-0.006; Step 2, adding a curing agent and mixing evenly, placing in a vacuum oven, evacuating to remove bubbles, the vacuum degree of the oven is ≤-90 kPa, curing at 80±5°C for 3 to 5 hours, to obtain a cross-linked polymer with uniformly distributed single-walled carbon nanotubes; Step 3, reacting the cross-linked polymer at 450-600° C. and vacuum degree ≤-90 kPa for 6-10 hours to obtain a polycarbosilane melt; Step 4: melt-spin the obtained polycarbosilane melt under the protection of an inert atmosphere and a negative pressure of 0.04 to 0.06 MPa, continuously feed the wire, sinter, and granulate to produce silicon carbide particles with a flexible network skeleton formed by interlacing and winding single-walled carbon nanotubes; wherein the wire feeding speed is 1 to 10 m / min, the sintering temperature is 1000 to 1500°C, and the sintering time is 2 to 6 hours.

2. The method for preparing the silicon carbide negative electrode material according to claim 1, characterized in that: The single-walled carbon nanotube has a diameter of 1-3 nm, a length of 2-5 μm, and an aspect ratio of 1000-5000.

3. The method for preparing the silicon carbide negative electrode material according to claim 2, characterized in that: The mass ratio of the curing agent to the polydimethylsiloxane prepolymer is 0.8-1.2:

10.

4. The method for preparing the silicon carbide negative electrode material according to claim 1, characterized in that: The diameter of the particles obtained by granulation in step 4 is 0.5 to 20 μm, and the length is 0.5 to 20 μm.

5. The method for preparing the silicon carbide negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 5, mixing the granules obtained by granulation with carbon powder and lithium perfluorosulfonic acid resin in a mass ratio of 1:0.5-2:0.02-0.1, adding an organic solvent to fully disperse them, and heating at 80-100°C for 4-6h; wherein the carbon powder is natural graphite or artificial graphite, and its D 50 1~5μm.

6. The method for preparing the silicon carbide negative electrode material according to claim 5, characterized in that: The organic solvent is N-methylpyrrolidone.

7. A silicon carbide negative electrode material, characterized in that: It is made by the method of any one of claims 1 to 6; its structure comprises silicon carbide particles, inside of which there are single-walled carbon nanotubes, which are interlaced and entangled to form a flexible network skeleton to bind the silicon carbide.

8. The silicon carbide negative electrode material according to claim 7, characterized in that: The silicon carbide particles are coated with carbon powder, and the carbon powder is bonded by lithiated perfluorosulfonic acid resin.

9. The silicon carbide negative electrode material according to claim 8, characterized in that: The carbon powder is graphite.